Drug resistance mechanisms in a high grade glioma cell line - Al-Ghafari, Ayat B. (2013)
Glioblastoma multiforme (GBM) is the most common and aggressive primary brain tumour. Despite advances in GBM treatment, there is a high frequency of local relapse due to the acquisition of drug resistance. Investigation of glioma cell lines will help us to understand the molecular basis of this hard to treat tumour. In this study, the rat C6 glioma cell line was used as a model alongside two drug selected derivatives (C6-etoposide and C6-irinotecan) to investigate the mechanisms of chemo-resistance in glioma by identifying candidate proteins, genes, and key signalling pathways. Proteomic (2D gel electrophoresis) and genomic (gene array) analyses were performed to determine protein and gene expression changes. Integration of this data with cellular pathway analysis resulted in the prediction that cellular migration and the response to oxidative stress would be distinct in the drug selected C6 cell lines. Cell migration was subsequently assessed using wound scratch repair and transwell migration assays, whilst the response to oxidative stress produced by reactive oxygen species was determined fluorimetrically. The C6 cell line exposed to irinotecan (DNA topoisomerase I inhibitor) showed reduced migration, even under the influence of chemoattractant, compared to other cell lines, consistent with alterations in the expression of collagen genes. The C6 cell line exposed to etoposide (DNA topoisomerase II inhibitor) showed greater resistance to oxidative stress which was proposed to be due to alterations in the signalling pathways downstream of the PTEN/PI3Kinase. Future studies, investigating the effect of PI3Kinase pathway inhibitors are considered and it is proposed that further research into this signalling pathway will be able to uncover the molecular basis of distinct chemo-resistance in this important model cell system for aggressive glioma.